Skrining Methicillin Resistant Staphylococcus aureus (MRSA) pada Tenaga Kesehatan Bangsal Melati 1, Melati 2, dan Mawar 2 RSUD Dr. Moewardi - Achmad Faiz Sulaiman; . Marwoto; . Purwoko (Nexus Biomedika, 2013)
Background: MRSA is known as one of main cause of nosocomial infection since found in 1961. In Indonesia, its prevalence reached 23,5%. Direct contact to healthcare workers can cause transmission of Staphylococcus aureus to patients. Carrier of chronic MRSA plays important roles on MRSA infection in hospital setting. This research aimed to know the incidence of MRSA nasal carriage of healthcare workers in RSUD Dr Moewardi Surakarta. Methods: This was an descriptive study using cross sectional design. Samples were taken from nasal swab of healtcare workers in wards of Melati 1, Melati 2 and Mawar 2. Samples were examined in Microbiology Laboratory of FK UNS. Total samples obtained were 74 according to total sampling theory. Data were analyzed descriptively and tested with Chi-Square tests. Results: The result of nasal swab from 26 healthcare workers in Melati 1 ward showed that there were 7 healthcare workers that were colonized by Staphylococcus aureus and one of them was MRSA case. In Melati 2 ward, from 25 healthcare workers, ten of them were colonized by Staphylococcus aureus and 8 out of 10 healthcare workers were MRSA cases. Whereas in Mawar 2 ward from nasal swab of 23 healthcare workers, six of them were colonized by Staphylococcus aureus and no MRSA case was found. Conclusions: The number of MRSA incidence in Melati 1, Melati 2 and Mawar 2 wards consecutively were 1.33%, 10.67% and 0%. Keywords: MRSA, healthcare worker, colonization.